Strengthening the scale‐up and uptake of effective interventions for sex workers for population impact in Zimbabwe. (22nd July 2019) - Cowan, Frances M; Chabata, Sungai T; Musemburi, Sithembile; Fearon, Elizabeth; Davey, Calum; Ndori‐Mharadze, Tendayi; Bansi‐Matharu, Loveleen; Cambiano, Valentina; Steen, Richard; Busza, Joanna; Yekeye, Raymond; Mugurungi, Owen; et al.
Abstract: Introduction: UNAIDS' goal of ending AIDS by 2030 is unreachable without better targeting of testing, prevention and care. Female sex workers (FSW) in Zimbabwe are at high risk of HIV acquisition and transmission. Here, we report on collated programme and research data from Zimbabwe's national sex work programme. We also assess the potential for wider population impact of FSW programmes by modelling the impact on HIV incidence of eliminating transmission through FSW (i.e. calculate the population attributable fraction of incidence attributable to sex work). Methods: Descriptive analyses of individual‐level programme data collected from FSW between 2009 and June 2018 are triangulated with data collected through 37 respondent driven sampling surveys from 19 sites in Zimbabwe 2011 to 2017. We describe programme coverage, uptake, retention and patterns of sex work behaviour and gaps in service provision. An individual‐level stochastic simulation model is used to reconstruct the epidemic and then the incidence compared with the counter‐factual trend in incidence from 2010 had transmission through sex work been eliminated from that date. Results: Sisters has reached >67, 000 FSW since 2009, increasing attendance as number of sites, programme staff and peer educators were increased. Over 57% of all FSW estimated to be working in Zimbabwe in 2017 (n = 40, 000) attended the programme at least once. The proportion of young FSW reached has increased with introduction of the "Young Sisters programme." There are no clear differences in pattern of sex work across settings. Almost all women report condom use with clients at last sex (95%); however, consistent condom use with clients in the last month varies from 52% to 95% by site. Knowledge of HIV‐positive status has increased from 48 to 78% between 2011 and 2016, as has prevalence of ART use among diagnosed women (29 to 67%). Although subject to uncertainty, modelling suggests that 70% (90% range: 32%, 93%) of all new infections in Zimbabwe from 2010 are directly or indirectly attributable to transmission via sex work. Conclusions: It is feasible to increase coverage and impact of sex work programming through community‐led scale‐up of evidence‐based interventions. Eliminating transmission through commercial sex would likely have a substantial impact on new infections occurring more widely across Zimbabwe.